Awareness on Radiation Protection Devices Among Dental Students - CHANDRASEKHAR, HARSHINEE; GANAPATHY, DHANRAJ; PANDURANGAN, KIRAN KUMAR; VELAYUDHAN, ASHOK (The journal of contemporary issues in business and government, 2020)
Radiation protection refers to the implementation of practices to reduce radiation exposure to patients, workers and the public. The fundamental aim of radiation protection is to reduce risk of harm by ensuring that any dose received is justified and ‘as low as reasonably practicable’ (ALARP). Exposure to Radiation has become common in Dentistry, patients are exposed to radiation by various radiation emitting devices such as OPG, CBCT,CT and IOPA. Apart from patients, dental surgeons and dental assistants are being exposed to radiations on a regular basis. Radiation effects on human cells cause various problems, increased risk of brain cancers, tumors of parotid gland and various problems in the head and neck region. Thus knowing about Radiation protection is important for both patients and Dentists.The Aim of this study is to create awareness and determine the understanding of radiation protection devices and its role in dentistry among dental students.Radiographic examination plays an important part of diagnosis in dental practice.Majority of the dental students within the study were aware of the radiation protection devices and its usage.